Governance for regenerative and decarbonised eco-city regions - Bunning, Jessica (Elsevier, 2014)
Today, world’s city populations are growing at an unprecedented rate. Old centralised, city infrastructure networks are under pressure to support the production, distribution and consumption of city resources. New distributed, low and zero carbon infrastructure options are required to reduce global carbon emissions and pollution, and improve the efficient distribution of energy, water and waste products and services. Similarly, new strategies to manage these infrastructure systems are required. Outdated political, economic, and social barriers need to be reviewed to allow city precincts to succeed in reducing their carbon footprint, improve people’s lifestyles, and live more harmoniously within the means of the Planet. This paper seeks to uncover some of the barriers, as well as the opportunities that exist for the process of decarbonising cities to succeed. The paper through a series of interviews with professionals from all different sectors of society, aims to shed some light on some of the key issues surrounding the topic of governance and decarbonised, urban development. The work also highlights some emerging business models that demonstrate the type of governance structures that can support decarbonised development within cities and regions.